Pengaruh Penjualan Dan Harga Pokok Penjualan Terhadap Laba Bersih - Denisa Nurazhari; Dailibas Dailibas (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The problems raised in this study are: analyzing, analyzing and analyzing the analysis and sales and cost of goods sold to net income. The listed companies in the cigarette manufacturing sub-sector were IDX 2011-2019. The number of samples taken were 4 (three) cigarette sub-sector companies from 5 cigarette company populations that had published complete annual financial reports during the study period. The sampling technique used was purposive sampling. This thesis is expected to contribute to the development of accounting, especially financial accounting. The research method used is descriptive quantitative method verivicative with multiple linear regression analysis. Based on the results of data analysis, the results were obtained; Sales have a significant positive effect on net income. And the Sales Price in a partial test has a negative effect on net income, on the same or simultaneous test, Sales and COGS are known to have a significant effect on Net Income. Keywords: Sales, COGS, Net Income,